EKSISTENSI PENDIDIKAN SWASTA DALAM UNDANG-UNDANG SISTEM PENDIDIKAN NASIONAL (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
Private education is part of a community-based education has a lot of acting to develop education in the country. There are still some things that need to be addressed by the Government, such as human resource development in private schools, proportionality in the allocation of education subsidies, and removing discrimination between private.education public schools with private schools contributed significantly to the intellectual life of the nation's efforts. The Government should have a positive commitment, positive commitment can be realized with a balanced policy between the government and the private land.